2015
DOI: 10.1002/qua.25006
|View full text |Cite
|
Sign up to set email alerts
|

Biphenyl: A stress tensor and vector-based perspective explored within the quantum theory of atoms in molecules

Abstract: We use quantum theory of atoms in molecules (QTAIM) and the stress tensor topological approaches to explain the effects of the torsion u of the C-C bond linking the two phenyl rings of the biphenyl molecule on a bond-by-bond basis using both a scalar and vector-based analysis. Using the total local energy density H(r b ), we show the favorable conditions for the formation of the controversial H-H bonding interactions for a planar biphenyl geometry. This bond-by-bond QTAIM analysis is found to be agreement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
74
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 33 publications
(54 reference statements)
6
74
0
Order By: Relevance
“…Thus, analogously to the QTAIM descriptor, we calculate a stress tensor stiffness, S σ = | λ 1 σ |/| λ 3 σ |, which has been found as a good descriptor of the “resistance” of the bond‐path to the twist, as well as the eigenvector, e 1 σ indicating the direction of the π‐bond . Previously, it was found that the stress tensor stiffness, S σ produced results that were in line with physical intuition …”
Section: Theory and Methodsmentioning
confidence: 76%
See 4 more Smart Citations
“…Thus, analogously to the QTAIM descriptor, we calculate a stress tensor stiffness, S σ = | λ 1 σ |/| λ 3 σ |, which has been found as a good descriptor of the “resistance” of the bond‐path to the twist, as well as the eigenvector, e 1 σ indicating the direction of the π‐bond . Previously, it was found that the stress tensor stiffness, S σ produced results that were in line with physical intuition …”
Section: Theory and Methodsmentioning
confidence: 76%
“…Therefore, the basin‐path set area is defined as the area of the surface swept out by the ∇ ρ ( r ) trajectories undergoing torsion. A recent investigation on biphenyl found that the basin‐path set areas of the C atomic basins defined by the e 2 eigenvector of the BCP undergoing a torsion φ was always greater than for the corresponding e 1 eigenvector except at the planar conformation, φ = 0.0° . The converse was found to be true for the H atomic basins associated with the H—H BCPs …”
Section: Theory and Methodsmentioning
confidence: 93%
See 3 more Smart Citations